Homogeneous nucleation rates of nitric acid dihydrate (NAD) at simulated stratospheric conditions – Part II: Modelling - O. Möhler; H. Bunz; O. Stetzer (Atmospheric Chemistry and Physics, 2006)
Activation energies ΔGact for the nucleation of nitric acid dihydrate (NAD) in supercooled binary HNO3/H2O solution droplets were calculated from volume-based nucleation rate measurements using the AIDA (Aerosol, Interactions, and Dynamics in the Atmosphere) aerosol chamber of Forschungszentrum Karlsruhe. The experimental conditions covered temperatures T between 192 and 197 K, NAD saturation ratios SNAD between 7 and 10, and nitric acid molar fractions of the nucleating sub-micron sized droplets between 0.26 and 0.28. Based on classical nucleation theory, a new parameterisation for ΔGact=A×(T ln SNAD)−2+B is fitted to the experimental data with A=2.5×106 kcal K2 mol−1 and B=11.2−0.1(T−192) kcal mol−1. A and B were chosen to also achieve good agreement with literature data of ΔGact. The parameter A implies, for the temperature and composition range of our analysis, a mean interface tension σsl=51 cal mol−1 cm−2 between the growing NAD germ and the supercooled solution. A slight temperature dependence of the diffusion activation energy is represented by the parameter B. Investigations with a detailed microphysical process model showed that literature formulations of volume-based (Salcedo et al., 2001) and surface-based (Tabazadeh et al., 2002) nucleation rates significantly overestimate NAD formation rates when applied to the conditions of our experiments.